Push-out tests of shear connectors in U-shaped steel–concrete composite girder. (June 2021) - Liu, Yong; Guo, Lanhui; Shi, Jun; Wang, Jingfeng
Highlights: Angle connectors welded to webs is recommended for U-shaped composite girder. Eurocode 4 is more suitable for predicting the stiffness of shear connectors. The shear strength of concrete interface could be conservatively predicted by Chinese Code. A formula is proposed to describe the load-slip curve of various shear connectors. Abstract: U-shaped steel–concrete composite girder has higher flexural resistance, more excellent fire resistance and better sound insulation due to the infilled concrete in U-shaped steel girder, compared with traditional composite beams. The existing researches indicated that U-shaped composite beams with shear connectors of headed studs and steel angles all exhibited good flexural performance. However, limited studies were conducted on shear resistance of angle-shaped connectors in U-shaped composite beams and then it is difficult to choose the more suitable shear connector for U-shaped composite beams. Therefore, push-out tests of different configuration of shear connectors were performed to determine their effectiveness in developing composite action in term of strength and load-slip behavior. In the tests, several options of shear connectors were examined including steel angle welded to webs, steel angles welded to flanges, headed studs, steel angle welded to webs working together with headed studs, and two separated steel plates welded to webs. The experimental results showed angle connectors welded to the webs of U-shaped girder possess higher shear resistance, larger slip capacity among all shear connectors. Combining with avoiding the congestion between shear connectors and longitudinal reinforcements, steel angles welded to the webs are recommended as shear connectors for U-shaped composite beams. At last, analytical formulas were proposed to describe the load-slip curves of different shear connectors and the design parameters obtained by regression analysis agreed well with the test results.